Dexter by design : a novel - Lindsay, Jeffry P. (Vintage crime/Black Lizard., 2010)
Newlywed blood-spatter analyst Dexter Morgan investigates the work of a Miami-area serial killer who has disguised his latest victim as a sunbather on the beach.